Glyphosate-Resistant Giant Ragweed (Ambrosia trifida) Control in Glufosinate-Resistant Soybean. (December 2014) - Kaur, Simranpreet; Sandell, Lowell D.; Lindquist, John L.; Jhala, Amit J.
Abstract : Glyphosate-resistant giant ragweed is one of the most competitive weeds of agronomic crops in the United States. Early emergence and rapid growth rate makes giant ragweed a competitive weed early in the season and reduces crop yields. Therefore, early spring control of giant ragweed using a preplant herbicide is critical. Glufosinate is an alternative POST herbicide for weed control in glufosinate-resistant soybean. Field experiments were conducted at David City, NE, in 2012 and 2013 to evaluate the efficacy of preplant herbicides followed by glufosinate applied alone or in tank mixes for control of glyphosate-resistant giant ragweed in glufosinate-resistant soybean. Preplant treatments containing 2, 4-D, flumioxazin, glufosinate, paraquat, saflufenacil, and sulfentrazone provided 79 to 99% control of giant ragweed 21 d after treatment (DAT), and subsequent application of glufosinate alone or in tank mixes resulted in 90 to 99% control at 21 DAT. Preplant application of S -metolachlor plus metribuzin or chlorimuron, flumioxazin plus thifensulfuron followed by glufosinate resulted in < 40% control of giant ragweed, and soybean yields were < 870 kg ha −1 . Although statistically comparable to several other treatments, preplant application of 2, 4-D or saflufenacil tank mixes followed by glufosinate resulted in the highest level of control (> 97%) and soybean yield (2, 624 to 3, 378 kg ha −1 ). This study confirms that preplant herbicide options are available for control of glyphosate-resistant giant ragweed, and a follow-up application of glufosinate will provide season-long control in glufosinate-resistant soybean.